190 CONNECTED HEALTH SUSTAINING HOME STAY IN DEMENTIA (CHESS): FACTORS ASSOCIATED WITH THE BURDEN EXPERIENCED BY CAREGIVERS OF PEOPLE WITH DEMENTIA. (25th October 2022) - Merriman, N; Mackey, L; Fernandez, EG; Curran, F; Caulfield, B; Power, D; O'Shea, D; Doyle, R; Blake, C
Abstract: Background: To date, little research has been carried out exploring the burden experienced by informal caregivers of People with Dementia (PwD). We explored factors that influence the burden experienced by caregivers of PwD over 12 months. Methods: Fifty-two PwD and their informal caregivers were recruited by convenience sampling to the "CHESS" Study. Data were collected at five time points over 12 months between April 2017 and November 2019. Mixed model analyses were used to investigate associations of caregiver burden (measured by the Zarit-Burden Interview; ZBI) with factors in four domains: 1) Psychological Well-Being (PWB; measures of anxiety, depression, and caregiver distress); 2) Social Capital and Resources (SCR; incorporating access to community-based health services, transportation needs, education level, occupation and living situation of the PwD, and employment status of the caregiver); 3) Physical Fitness and Health (PFH; including the Quantitative Timed Up and Go (QTUG), baseline grip strength, indices of frailty, sensory acuity); and Managing Everyday life with Dementia (MED; incorporating measures of cognition, behavioural disturbances, functional ability, and indices of dependence of PwD. Results: Across all domains, caregiver burden significantly increased over time (p<0.001) and less burden was experienced by caregivers of older PwD (p<0.05). In PWB, higher caregiver depression levels predicted higher levels of caregiver burden (p=0.033). In the SCR domain, caregivers of PwD who were independent in their transport needs experienced lower levels of burden (p=0.002). No other factors within the PFH or MED domains reached significance in predicting caregiver burden. Conclusion: This longitudinal analysis elucidates potential predictors of caregiver burden and highlights the need for future research to be carried out in this area. In particular, psychological well-being in caregivers was shown to significantly impact on the experience of burden. Interventions to alleviate caregiver burden should be tailored to include support for psychological well-being.